2021
DOI: 10.1021/acsearthspacechem.1c00255
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Volatility-Based Aerosol Phase State Predictions in the Amazon Rainforest

Abstract: Organic aerosol (OA) is a complex matrix of various constituentsfresh (primary organic aerosolsPOA) and aged via oxidation (secondary organic aerosolsSOA), generated from biogenic, anthropogenic, and biomass burning sources. The viscosity of OA can be critical in influencing new particle formation, reactive uptake processes that impact evaporation-growth kinetics, and the lifetime of particles in the atmosphere. This work utilizes a well-defined relationship between volatility and viscosity for pure compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 99 publications
1
34
0
Order By: Relevance
“…We calculated the viscosity of OA (η org ) based on the glass transition temperature of OA (T g,org ), which is essentially the temperature at which the transition to the amorphous solid-phase state occurs. 23 Viscosity was calculated online at each WRF-Chem model time step and grid cell as a function of temperature, RH, and OA composition (volatility and O/C ratio), as described in Rasool et al, 24 and further details of these calculations are provided in the Supporting Information. Calculations of OA viscosity and particle-phase diffusivity are performed.…”
Section: ■ Methodsmentioning
confidence: 99%
“…We calculated the viscosity of OA (η org ) based on the glass transition temperature of OA (T g,org ), which is essentially the temperature at which the transition to the amorphous solid-phase state occurs. 23 Viscosity was calculated online at each WRF-Chem model time step and grid cell as a function of temperature, RH, and OA composition (volatility and O/C ratio), as described in Rasool et al, 24 and further details of these calculations are provided in the Supporting Information. Calculations of OA viscosity and particle-phase diffusivity are performed.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The T g values measured here refer to dried aerosol samples with the main component being glyoxal, i.e., without the presence of water. Nevertheless, such experimentally determined values are crucial for the parametrization development and subsequent modeling of the phase state or viscosity of atmospherically relevant particles. ,, Our results also indicate the importance for implementing more complex aqueous phase chemistry in such models, rather than applying simplified mixing rules. At colder temperatures, the equilibration time of aqueous glyoxal aerosol droplets after water uptake or loss is longer than at room temperature.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 80%
“…These effects have been previously shown in laboratory studies by measuring the viscosity of organic and inorganic mixtures (Dette and Koop, 2015;Power et al, 2013;Rovelli et al, 2019;Saukko et al, 2012;Schill and Tolbert, 2014;Song et al, 2021;Wang et al, 2015) and in ambient samples (Liu et al, 2019;Slade et al, 2019). Moreover, the effects of internally mixed inorganics on the particle's viscosity are not considered in current climate models (Rasool et al, 2021;Schmedding et al, 2020;Shiraiwa et al, 2017). These liquid particles are expected to be less stable and have faster 490 heterogeneous reaction rates, be more reactive, and be quickly photodegraded in the FT (Berkemeier et al, 2016;Kuwata and Martin, 2012;Lienhard et al, 2015;Liu et al, 2018a;Marshall et al, 2016;Pöschl and Shiraiwa, 2015b;Renbaum-Wolff et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…DeRieux et al, 2018 predicted the viscosity of 400 biomass burning particles using their chemical composition, and they found that the viscosity of biomass burning particles varied between 10 -2 Pa S and 10 12 Pa S depending on the RH. Liu et al, 2021 found that ambient and lab-generated biomass burning particles are in a non-solid state at RH between 20 % and 50 %. Therefore, these studies support our finding that biomass burning can emit particles with a broad viscosity distribution.…”
Section: Phase State Of Particles At the Omp Sitementioning
confidence: 99%